2020
DOI: 10.21203/rs.3.rs-126768/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Scopolamine-induced Delirium Promotes Neuroinflammation and Neuropsychiatric Disorder in Mice

Abstract: BackgroundPostoperative delirium is a common neuropsychiatric syndrome resulting in a high postsurgical mortality rate and decline in postdischarge function. Extensive research has been performed on both human and animal delirium models due to their clinical significance, focusing on systemic inflammation and consequent neuroinflammation playing a key in the pathogenesis of postoperative cognitive dysfunctions. Since animal models are widely utilized for pathophysiological study of neuropsychiatric disorders, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…In the present study, scopolamine-treated mice showed a significant increase in COX-2 activity which was reduced by pretreatment with the S2 extract. The NLRP3 inflammasome, an intracellular sensor that detects a broad range of microbial motifs, increases the levels of pro-inflammatory cytokines such as IL-1β in the brain [ 33 ], promotes the aggregation of innate immune cells, such as microglia, initiates the downstream inflammatory cascade, and accelerates the pathological progression of neurodegenerative diseases [ 34 ]. Its activation has been used as a marker for mobilizing immune defense mechanisms in various inflammatory diseases and the development of neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, scopolamine-treated mice showed a significant increase in COX-2 activity which was reduced by pretreatment with the S2 extract. The NLRP3 inflammasome, an intracellular sensor that detects a broad range of microbial motifs, increases the levels of pro-inflammatory cytokines such as IL-1β in the brain [ 33 ], promotes the aggregation of innate immune cells, such as microglia, initiates the downstream inflammatory cascade, and accelerates the pathological progression of neurodegenerative diseases [ 34 ]. Its activation has been used as a marker for mobilizing immune defense mechanisms in various inflammatory diseases and the development of neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 99%